ANTIOXIDANT ACTIVITY TEST OF BALAKACIDA LEAVES (Chromolaena odorata L) WITH DPPH (2,2-difenil-1-pikrilhidrazil) METHOD - Elsya Martia; Munir Alinu Mulki; Lina Nurfadhila (Jurusan Kimia FMIPA Universitas Lampung, 2024)
Balakacida leaves (Chromolaena odorata L) are plants known for their allelopathic properties, which can be utilized as natural herbicides. Empirically, they are used as wound healing agents, mouthwash, anti-diarrheal, antimicrobial, and anti-inflammatory medicines. The leaves are processed by squeezing them to extract their liquid, which is then applied to skin wounds for treatment (Marianne, 2014). Flavonoid components in balakacida leaves have antimicrobial effects. The focus of this research is to determine the IC50 value of balakacida leaves and characterize their antioxidant ability. Multi-step maceration using polarity-based solvents (n-hexane, ethyl acetate, and ethanol) is employed for extraction. The DPPH technique is utilized to evaluate antioxidant capacity. Phytochemical analysis has revealed active secondary metabolites with antioxidant properties in the plant, including tannins, flavonoids, alkaloids, and steroids. The IC50 values for n-hexane, ethyl acetate, and ethanol extracts are 35.58, 14.24, and 12.73 ppm respectively, indicating very high antioxidant activity. According to Fitrah (2017), crude balakacida leaf extract exhibits antioxidant effects. These effects are attributed to the high content of flavonoids, which possess antioxidant activity capable of inhibiting the oxidation process.